Thyroid hormone induction of human cholesterol 7 alpha-hydroxylase (Cyp7a1) in vitro - Lammel Lindemann, Jan A. (2014)
Thyroid hormone (TH) modulates serum cholesterol by acting on TH receptor β1 (TRβ1) in liver to regulate metabolic gene sets. In rodents, one important TH regulated step involves induction of Cyp7a1, an enzyme in the cytochrome P450 family, which enhances cholesterol to bile acid conversion and plays a crucial role in regulation of serum cholesterol levels. Current models suggest, however, that Cyp7a1 has lost the capacity to respond to THs in humans. We were prompted to re-examine TH effects on cholesterol metabolic genes in human liver cells by a recent study of a synthetic TH mimetic which showed that serum cholesterol reductions were accompanied by increases in a marker for bile acid synthesis in humans. Here, we show that TH effects upon cholesterol metabolic genes are almost identical in mouse liver, mouse and human liver primary cells and human hepatocyte cell lines. Moreover, Cyp7a1 is a direct TR target gene that responds to physiologic TR levels through a set of distinct response elements in its promoter. These findings suggest that THs regulate cholesterol to bile acid conversion in similar ways in humans and rodent experimental models and that manipulation of hormone signaling pathways could provide a strategy to enhance Cyp7a1 activity in human patients.